2004
DOI: 10.1128/jb.186.1.90-97.2004
|View full text |Cite
|
Sign up to set email alerts
|

Flavin Mononucleotide-Binding Flavoprotein Family in the Domain Archaea

Abstract: The protein (AfpA, for archaeoflavoprotein) encoded by AF1518 in the genome of Archaeoglobus fulgidus was produced in Escherichia coli and characterized. AfpA was found to be a homodimer with a native molecular mass of 43 kDa and containing two noncovalently bound flavin mononucleotides (FMNs). The cell extract of A. fulgidus catalyzed the CO-dependent reduction of AfpA that was stimulated by the addition of ferredoxin. Ferredoxin was found to be a direct electron donor to purified AfpA, whereas rubredoxin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…afpA appears to encode a novel dihydromethanopterin reductase. Ding and Ferry have recently purified an AfpA homolog from A. fulgidus and demonstrated that it is an FMN-binding electron carrier protein (8). These authors also analyzed the distribution of AfpAs in prokaryotes based on the genomic sequences available at the time and concluded that these were restricted to methanogenic archaea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…afpA appears to encode a novel dihydromethanopterin reductase. Ding and Ferry have recently purified an AfpA homolog from A. fulgidus and demonstrated that it is an FMN-binding electron carrier protein (8). These authors also analyzed the distribution of AfpAs in prokaryotes based on the genomic sequences available at the time and concluded that these were restricted to methanogenic archaea.…”
Section: Discussionmentioning
confidence: 99%
“…However, one additional gene is present upstream of orf20, having homologs in Archaea, encoding a conserved archaeal flavoprotein (afpA) (8). In addition to the two gene islands, three other archaeal gene homologs were found in the genome.…”
Section: Gene Islands Encoding H 4 Mpt-linked C 1 Transfer Reactions mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to M. barkeri, Methanosarcina acetivorans lacks the Ech hydrogenase (11). It can nevertheless grow on acetate, which is why another complex present in this organism, the Rnf complex, is thought to be involved in the aceticlastic pathway of methanogenesis as an acceptor for Fd red (8,10,17). The Methanosarcina mazei genome, however, contains genes coding for the Ech hydrogenase, but this species lacks the Rnf complex (5).…”
mentioning
confidence: 99%
“…Genome sequencing has revealed that some betaproteobacteria also lack the dmrA gene but contain instead an additional gene (afpA) coding for an archaealflavoprotein-like flavoprotein (AfpA) of undetermined function (22,23). The bacterial AfpA homolog contains a predicted flavin mononucleotide (FMN)-binding site but lacks a recognizable binding site for other cofactors.…”
mentioning
confidence: 99%